Investigation on thermo-physical properties of liquid In-Tl alloy - Bhandari, I B; Panthi, N; Koirala, I (BIBECHANA, 2021)
This research explores the mixing behavior of liquid In – Tl system through thermodynamic and the structural properties on the basis of Complex Formation Model. The properties like surface tension and viscosity have been analyzed through a simple statistical model and Moelwyn – Hughes equation. The interaction parameters are found to be positive, concentration-independent, and temperature-dependent. Theoretical results are in good agreement with the corresponding literature data which support homo-coordinating tendency in the liquid In-Tl alloy. BIBECHANA 18 (1) (2021) 149-158